Från ”tandborstord” till ”memilord” – om nyord och deras belägg - Jansson, Håkan (Nordiske Studier i Leksikografi, 2018)
This presentation describes an inquiry into recent neologisms in Swedish as presented by Språkrådet (‘Language Council of Sweden’) and Språktidningen (‘the Language magazine’). Lists of neologisms from 2004 to 2014 has been excerpted and studied together with corresponding language examples. The study shows that the share of in corpora un-attested or only meta use attested neologisms has risen to around one fourth of the total in recent years.